Family and species as determinants modulating mineral composition of selected wild-growing mushroom species - Mleczek, Mirosław; Budka, Anna; Kalač, Pavel; Siwulski, Marek; Niedzielski, Przemysław (Environmental science and pollution research international, 2021)
It has been known since the 1970s that differences exist in the profile of element content in wild-growing mushroom species, although knowledge of the role of mushroom species/families as determinants in the accumulation of diverse element remains limited. The aim of this study was to determine the content of 63 mineral elements, divided into six separate groups in the fruit bodies of 17 wild-growing mushroom species. The mushrooms, growing in widely ranging types of soil composition, were collected in Poland in 2018. Lepista nuda and Paralepista gilva contained not only the highest content of essential major (531 and 14,800 mg kg-1, respectively of Ca and P) and trace elements (425 and 66.3 mg kg-1, respectively of Fe and B) but also a high content of trace elements with a detrimental health effect (1.39 and 7.29 mg kg-1, respectively of Tl and Ba). A high content of several elements (Al, B, Ba, Bi, Ca, Er, Fe, Mg, Mo, P, Sc, Ti or V) in L. nuda, Lepista personata, P. gilva and/or Tricholoma equestre fruit bodies belonging to the Tricholomataceae family suggests that such species may be characterised by the most effective accumulation of selected major or trace elements. On the other hand, mushrooms belonging to the Agaricaceae family (Agaricus arvensis, Coprinus comatus and Macrolepiota procera) were characterised by significant differences in the content of all determined elements jointly, which suggests that a higher content of one or several elements is mushroom species-dependent. Graphical abstract.
Keywords: Poland; Mushroom species; Agaricus; Minerals; Mineral elements; Mushroom family; minerály; Agaricales; lidé; Coprinus; Polsko; Humans; Accumulation; Wild-growing mushrooms